1978
DOI: 10.3171/jns.1978.49.5.0764
|View full text |Cite
|
Sign up to set email alerts
|

Intradural sacral nerve root metastasis mimicking herniated disc

Abstract: Spinal tumors may mimic herniated discs but the neurological findings and radiographs usually indicate the correct diagnosis. A case of metastasis to the S-1 intradural nerve rootlets is reported, with symptoms closely simulating a herniated disc. The correct diagnosis could not be made preoperatively in spite of clinical suspicion of a tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…Since 1950, 49 patients (excluding those in the M. D. Anderson Cancer Center series) with such tumors have been reported, with histological confirmation by surgery. 2,3,7,[9][10][11][12][13]16,17,19,[24][25][26][27][28][32][33][34][35][36][37]42,45 The average age of 54 years at diagnosis (range 23-74 years) is similar to that found in both the present study (mean age 51 years) and in the only other published series of significant size reported by Perrin and colleagues 23,34 in 1982. Women outnumbered men in both series by 6:4, and the female/male ratio is 1.3:1 when all 59 cases now on record are considered.…”
Section: Review Of the Literaturesupporting
confidence: 87%
“…Since 1950, 49 patients (excluding those in the M. D. Anderson Cancer Center series) with such tumors have been reported, with histological confirmation by surgery. 2,3,7,[9][10][11][12][13]16,17,19,[24][25][26][27][28][32][33][34][35][36][37]42,45 The average age of 54 years at diagnosis (range 23-74 years) is similar to that found in both the present study (mean age 51 years) and in the only other published series of significant size reported by Perrin and colleagues 23,34 in 1982. Women outnumbered men in both series by 6:4, and the female/male ratio is 1.3:1 when all 59 cases now on record are considered.…”
Section: Review Of the Literaturesupporting
confidence: 87%
“…It has been reported that an isolated intradural metastasis might simulate lumbar disc disease. 14,23 As in this case, back pain that increases with recumbency and keeps the patient awake at night together with bilateral sciatica are symptoms indicative of a possible intradural source. 8 Based on the previous descriptions, it is apparent that the cauda equina is an exceedingly rare site of metastasis of RCC.…”
Section: Discussionmentioning
confidence: 92%
“…Em uma breve revisão sobre o assunto, Perrin et al 2 encontraram 9 de 10 casos envolvendo o cone medular e a cauda equina, embora autores de uma revisão mais recente tenham identificado casos na junção cervicotorácica, sendo disseminados pela via hematogênica, extensão direta do espaço epidural, disseminação pelos vasos linfáticos perineurais e líquor. 2,3,8,9 No entanto, alguns autores 2,9 acreditam que o principal mecanismo de disseminação seja pelo líquor, baseados no fato de que 80% destas metástases espinhais serem sincrônicas com metástases cerebrais, 2,4 o que não foi observado em nosso caso.…”
Section: Discussionunclassified